PENYUNTINGAN CUTTO CUT DAN COMPOSITING VIDEO MUSIK PANTAIKU KALAMASOUL BAND - Ambarwati, Endang Retno; Waskito, Setyo Bagus (Capture : Jurnal Seni Media Rekam, 2012)
There are a lot of reggae musics that can be taken advantage,among them can be usedas a means of delivering a moral message,voice calling for weak communities,provide relaxationand well able to bring a message of peace for others.Departing from this fact,producer seeks tocreate two music videos using different construction techniques, the Cut to Cut technique andCompositing technique to eliminate negative view of reggae musics and the choice was on mybeach songs created and sung by Kalamasoul Band.The Cut to Cut technique to arouse feelingsand emotions of the audience,so the audience feel being at the beach and can capture the moralmessages in the videos my beach music easily.The Compositing techniques to provide a varietyof different and interesting spectacle for the community that after seeing the music video, theaudience is not immediately forgotten of what he had just seen. Cultivation of the Pantaikumusic videos through three main stages, namely editing offline, online editing, and mixing. Byusing two different techniques on the same music,it turns out Pantaiku music video compositingtechniques packaging more attractive and entertaining. But seen from the delivery of themessage,the music video by cut to cut technique in my beach songs was more communicativeand easily received by the audience.Objective of the video was to create good music and finallyactractively reached.Keywords:Editing,cut to cut,compositing,Kalamasoul Band,dan Pantaiku